Key technologies for 5G wireless systems - Wong, Vincent W. S.; Cambridge University Press (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2017)
"Gain a detailed understanding of the protocols, network architectures and techniques being considered for 5G wireless networks with this authoritative guide to the state of the art. Get up to speed with key topics such as cloud radio access networks, mobile edge computing, full duplexing, massive MIMO, mmWave, NOMA, Internet of things, M2M communications, D2D communications, mobile data offloading, interference mitigation techniques, radio resource management, visible light communications, and smart data pricing. Learn from leading researchers in academia and industry about the most recent theoretical developments in the field. Discover how each potential technology can increase the capacity, spectral efficiency, and energy efficiency of wireless systems. Providing the most comprehensive overview of 5G technologies to date, this is an essential reference for researchers, practicing engineers and graduate students working in wireless communications and networking"--
Machine generated contents note: 1. Overview of new technologies for 5G systems Vincent W.S. Wong, Robert Schober, Derrick Wing Kwan Ng and Li-Chun Wang; Part I. Communication Network Architectures for 5G Systems: 2. Cloud radio access networks for 5G systems Chih-Lin I, Jinri Huang, Xueyan Huang, Rongwei Ren and Yami Chen; 3. Fronthaul-aware design for cloud radio-access networks Liang Liu, Wei Yu and Osvaldo Simeone; 4. Mobile edge computing Ben Liang; 5. Decentralized radio resource management for dense heterogeneous wireless networks Abolfazl Mehbodniya and Fumiyuki Adachi; Part II. Physical Layer Communication Techniques: 6. Non-orthogonal multiple access (NOMA) for 5G systems Wei Liang, Zhiguo Ding and H. Vincent Poor; 7. Flexible physical layer design Maximilian Matthe, Martin Danneberg, Dan Zhang and Gerhard Fettweis; 8. Distributed massive MIMO in cellular networks Michail Matthaiou and Shi Jin; 9. Full-duplex protocol design in 5G networks Taneli Riihonen and Risto Wichman; 10. Millimeter wave communications for 5G networks Jiho Song, Miguel R. Castellanos and David J. Love; 11. Interference mitigation techniques in wireless networks Koralia N. Pappi and George K. Karagiannidis; 12. Physical layer caching with limited backhaul in 5G Systems Vincent Lau, An Liu and Wei Han; 13. Cost-aware cellular networks powered by smart grid and energy harvesting Jie Xu, Lingjie Duan and Rui Zhang; 14. Visible light communication in 5G Harald Haas and Cheng Chen; Part III. Network Protocols, Algorithms, and Design: 15. Massive MIMO scheduling protocols Giuseppe Caire; 16. Mobile data offloading for heterogeneous wireless networks Man Hon Cheung, Haoran Yu and Jianwei Huang; 17. Cellular 5G access for massive Internet of Things German C. Madueno, Nuno Pratas, Cedomir Stefanovic and Petar Popovski; 18. Medium access control, resource management, and congestion control for M2M systems Shao-Yu Lien and Hsiang Hsu; 19. Energy-harvesting based D2D communication in heterogeneous networks Howard H. Yang, Jemin Lee and Tony Q.S. Quek; 20. LTE-unlicensed: overview and distributive coexistence design Yunan Gu, Lin X. Cai, Lingyang Song and Zhu Han; 21. Scheduling for millimeter wave networks Lin X. Cai, Lin Cai, Xuemin Shen and Jon W. Mark; 22. Smart data pricing in 5G systems Carlee Joe-Wong, Liang Zheng, Sangtae Ha, Soumya Sen, Chee Wei Tan and Mung Chiang.
Includes bibliographical references and index.
Keywords: Wireless communication systems; Machine-to-machine communications; Internet of things